Recruiting marijuana-exposed maternal-infant dyads for longitudinal study: a feasibility assessment - Sojin, Nayana A.; Parimoo, Rhea; Agliano, Lauren A.; Goodin, Amie J.; Varma, Deepthi S.; Goldberger, Bruce A.; Tuna, Ibrahim; Abu-Rustum, Reem; Roussos-Ross, Kay (Frontiers in Psychiatry, 2025)
IntroductionIn-utero marijuana exposures are correlated with adverse neurodevelopmental outcomes in exposed neonates. As rates of marijuana use in pregnancy and postpartum reportedly increase, it is crucial to obtain conclusive, pregnancy-specific safety data through well-designed clinical research studies. The objective of this study is to assess feasibility of recruitment and retention of marijuana-exposed pregnant women for longitudinal study involving biospecimen and imaging collection.MethodsParticipants self-reporting marijuana use in pregnancy and controls with no self-reported exposure were recruited from routine prenatal care in a large health-system. Consented participants completed imaging and biological specimen collections during pregnancy, at delivery, and postpartum. Proportions of collected samples/images at each data collection interval were calculated and compared for exposed versus unexposed.Results30 participants were recruited over 20 months: 77% (n=23) self-reported as marijuana-exposed and 23% (n=7) reported as unexposed (control). 70% (n=21) of participants completed the study (n=14 marijuana-exposed; n=7 control), while 30% (n=9 marijuana-exposed; 0%, n=0 control) completed some study visits before becoming lost-to-follow-up (LTFU).DiscussionPreliminary findings suggest that it is feasible to recruit and retain pregnant women using marijuana for longitudinal study. Although marijuana-exposed participants were more likely than control participants to miss postpartum visits, become LTFU, and require rescheduling of study visits, marijuana-exposed participants were still found to complete 68% of study visits.